2017
DOI: 10.18632/oncotarget.15434
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies SGCD and ACVRL1 mutations associated with total anomalous pulmonary venous return (TAPVR) in Chinese population

Abstract: As a rare type of Congenital Heart Defects (CHD), the genetic mechanism of Total Anomalous Pulmonary Venous Return (TAPVR) remains unknown, although previous studies have revealed potential disease-driving regions/genes. Blood samples collected from the 6 sporadic TAPVR cases and 81 non-TAPVR controls were subjected to whole exome sequencing. All detected variations were confirmed by direct Sanger sequencing. Here, we identified 2 non-synonymous missense mutations: c.C652T, p.R218W in activin A receptor type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…1,2 Patients with scimitar syndrome and multiple congenital anomalies can be challenging to manage due to their multiple organ system pathologies.Although some forms of CHD have been linked to various genetic syndromes, the mechanisms that contribute to scimitar syndrome remains elusive. [3][4][5][6][7][8][9] Studies have demonstrated an association between scimitar syndrome and extracardiac anomalies including congenital diaphragmatic hernia, imperforate anus, and variants of VACTERL association. [10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified.…”
mentioning
confidence: 99%
“…1,2 Patients with scimitar syndrome and multiple congenital anomalies can be challenging to manage due to their multiple organ system pathologies.Although some forms of CHD have been linked to various genetic syndromes, the mechanisms that contribute to scimitar syndrome remains elusive. [3][4][5][6][7][8][9] Studies have demonstrated an association between scimitar syndrome and extracardiac anomalies including congenital diaphragmatic hernia, imperforate anus, and variants of VACTERL association. [10][11][12][13][14] Although pathogenic variants in specific genes can clearly cause CHDs, the genetic factors contributing to most cases of scimitar syndrome remain unidentified.…”
mentioning
confidence: 99%
“…ABAT , CYFIP2 , FN1 and TEK are all expressed in vascular and lung tissue, EMP2 , FN1 and TEK are expressed in tracheal tissue (UniGene cDNA sources). Four further genes intersect between cytoskeleton and blood flow: AAMP (angio-associated migratory cell protein) is associated with angiogenesis and has potential roles in endothelial tube formation and the migration of endothelial cells, KCNMA1 (potassium calcium-activated channel subfamily M α 1), RAP1GDS1 (Rap1 GTPase-GDP dissociation stimulator 1) and SGCD (sarcoglycan delta) are associated with total anomalous pulmonary venous return [33].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al analysed whole exome sequencing (WES) data from 6 sporadic TAPVC cases and 81 non-TAPVC counterparts, providing evidence for ACVRL1 as a known causative gene and for SGCD as a candidate TAPVC gene [9]. Nash et al used WGS analysis to identify a nonsynonymous variant in RBP5 gene that was predicted to be deleterious and overrepresented in TAPVC [10].…”
Section: Introductionmentioning
confidence: 99%